PROFITABILITY ANALYSIS FOR MEASUREMENT OF FINANCIAL PERFORMANCE OF THE WOMEN'S MULTI-BUSINESS COOPERATIVE "DIAN WANITA" PASURUAN - Mardianto, Totok (Ecopreneur.12, 2023)
This research aims to analyze the financial performance of the Pasuruan Women's Multi-Enterprise Cooperative "Dian Wanita", when viewed from a profitability perspective using the Net Profit Margin Ratio, Benefits to Assets Ratio, and Benefits to Capital Ratio for 2014 - 2016. The type of research is descriptive qualitative. Research data was obtained from the Koperasi “Dian Wanita” Pasuruan  Financial report for 2021 - 2023. Data analysis is by calculating the profitability ratio using the formula Net Profit Margin Ratio, Benefits to Assets Ratio, and Benefits to Capital Ratio. Financial performance measurement is based on KUKM Ministerial Regulation Number 06/Per/M.KUKM/V/2006. The results of the research show that: 1) The financial performance of the Multi-Business Women's Cooperative "Dian Wanita" Pasuruan when viewed from the profitability side with unhealthy conditions, 2) The financial performance of the Multi-Enterprise Women's Cooperative "Dian Wanita" Pasuruan when viewed from the profitability side using the Ratio Benefits on assets, in 2021, 2022 and 2023 are in a healthy condition, 3) The financial performance of the Pasuruan Women's Multi-Enterprise Cooperative "Dian Wanita" when viewed from a profitability perspective using the Benefits to Capital Ratio, in 2021, 2022 and 2023 is in a healthy conditionThe results of this research show that the net profit margin ratio in 2021 - 2023 has a less healthy performance, so that the management of the Pasuruan Women's All-Business Cooperative "Dian Wanita" is required to be able to further increase the net profit margin by increasing product selling prices, reducing the cost of goods sold a, or by reducing the cooperative's operational burden so that it can increase the resulting net profit